Pengaruh Pengelolaan Sistem Informasi Manajemen Berbasis Komputer terhadap Produktivitas Kerja Karyawan di Pondok Pesantren Ummul Masakin Kabupaten Batanghari - Jamaludin Jamaluddin; Dian Nisa Istofa; Nur Annisah (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the influence of computer-based management information system management on productivity in Madrasah Aliyah Pondok Pesantren Ummul Masakin. This research is a quantitative study using a correlational research design, while the data analysis technique uses normality and product moment correlation tests. The results of this study found that in the 12 employees who were sampled there were results of product moment correlation testing, it was found that at the significance level of 5% = 0.576 and at the significance level of 1% = 0.708 it was rejected and accepted.